Berberine Inhibits MDA-MB-231 Cells as an Agonist of G Protein-Coupled Estrogen Receptor 1 - Miaomiao Qi (MDPI AG, 2021)
G protein-coupled estrogen receptor 1 (GPER1) is a potential therapeutic target for treating triple-negative breast cancers (TNBC). However, modulators for GPER1 that can be used to treat TNBC have not appeared. Berberine (BBR) is a bioactive isoquinoline alkaloid with high oral safety. In recent years, BBR has shown an inhibitory effect on TNBC tumors such as MDA-MB-231, but the molecular target remains unclear, which hinders related clinical research. Our work proved that BBR is a modulator of GPER1 that can inhibit cell viability, migration, and autophagy of MDA-MB-231 cells. The inhibitory effect of BBR on MDA-MB-231 cells has a dependence on estrogen levels. Although BBR promoted the proteasome, which is a major factor in the degradation of GPER1, it could still induce the protein level of GPER1. Correspondingly, the transcription of cellular communication network factor 2 (CCN2) was promoted. BBR could bind to GPER1 directly and change the secondary structure of GPER1, as in the case of 17β-estradiol (E2). In addition, BBR induced not only a high degree of co-localization of GPER1 and microtubule-associated protein 1 light chain 3 (MAP1LC3), but also the accumulation of sequestosome 1 (SQSTM1/p62) by the inhibition of the nuclear translocation of the nuclear factor-kappa B (NF-κB) subunit (RELA/p65), which indicates NF-κB inhibition and anti-cancer effects. This result proved that the promotional effect of BBR on the GPER1/NF-κB pathway was closely related to its inhibitory effect on autophagy, which may serve as a new mechanism by which to explain the inhibitory effect of BBR on MDA-MB-231 cells and expand our understanding of the function of both BBR and GPER1.